AL-FAJAR BERSERI FOUNDATION PREACHING STRATEGY IN DEVELOPING THE LIFE SKILLS OF PEOPLE WITH MENTAL REHABILITATION - Madeni Madeni; Ahmad Yahya (Jurnal Bina Ummat: Membina dan Membentengi Ummat, 2022)
Research purposes: This study aims to determine the da'wah strategy applied by the Al-Fajar Berseri Foundation to people with mental rehabilitation or ODGJ (People with Mental Disorders) with the strategies applied to them so that it can also be applied to people with mental rehabilitation who are outside , or if it can be applied to other normal people. Research Methods: The method used in this research is using qualitative methods using purposive sampling data analysis techniques combined with the Miles & Huberman interaction analysis model with the theory of da'wah strategy proposed by Al-Bayanuni, namely by taking some samples from a large number of representatives of the population to explore further important information regarding the strategy of da'wah and coaching and mental recovery of people with mental disabilities into other normal people. Conclusion: In the results of this study, it was found that the strategy carried out by the Al-Fajar Bereri Foundation for people with mental rehabilitation, there were at least 2 stages, 1. At this stage, the chairman of the Al-Fajar Bereri Foundation, namely Marsan Susanto, gave water ruqyah, massage and massage and traditional ingredients. 2. And in the second stage this is done by the coaches by providing educational offerings such as the Koran, learning to pray, managing daily personality, sports, singing, etc. At this stage, the Chairperson of the Al-Fajar Bereri Foundation, namely Marsan Susanto, provides ruqyah water, massage and massage and traditional ingredients. 2. And in the second stage this is done by the coaches by providing educational offerings such as the Koran, learning to pray, managing daily personality, sports, singing, etc. At this stage, the Chairperson of the Al-Fajar Bereri Foundation, namely Marsan Susanto, provides ruqyah water, massage and massage and traditional ingredients. 2. And in the second stage this is done by the coaches by providing educational offerings such as the Koran, learning to pray, managing daily personality, sports, singing, etc.